2012
DOI: 10.1177/1091581812460409
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of 1,2-Glycols as Used in Cosmetics

Abstract: Caprylyl glycol and related 1,2-glycols are used mostly as skin and hair conditioning agents and viscosity agents in cosmetic products, and caprylyl glycol and pentylene glycol also function as cosmetic preservatives. The Cosmetic Ingredient Review (CIR) Expert Panel noted that, while these ingredients are dermally absorbed, modeling data predicted decreased skin penetration of longer chain 1,2-glycols. Because the negative oral toxicity data on shorter chain 1,2-glycols and genotoxicity data support the safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…The solvent 1-2P is a short chain 1, 2-glycol that is used mainly as a skin conditioning and viscosity increasing agent in topical products (Johnson et al, 2012). There is only limited information in the literature regarding its action on the skin and its ability to act as a penetration enhancer has not been established.…”
Section: Permeation Studies Using Neat Solventsmentioning
confidence: 99%
“…The solvent 1-2P is a short chain 1, 2-glycol that is used mainly as a skin conditioning and viscosity increasing agent in topical products (Johnson et al, 2012). There is only limited information in the literature regarding its action on the skin and its ability to act as a penetration enhancer has not been established.…”
Section: Permeation Studies Using Neat Solventsmentioning
confidence: 99%
“…Non-esterified 1,2-diols are frequently used as skin and hair conditioning agents, viscosity-and foam-increasing agents [28][29][30]. They have bacteriostatic activities against a broad range of strains, which makes them useful as a treatment of skin diseases caused by bacteria, such as acne [31][32][33], and they are also suggested as a prophylaxis and/or treatment of fungal skin infections [34].…”
Section: Introductionmentioning
confidence: 99%
“…The safety of the preservative agent 1,2-hexanediol has been previously evaluated, and it has been shown not to cause significant skin irritation, sensitization or photosen-sitization (Johnson et al 2012). The MIC determination results showed that 1,2-hexanediol was active at concentrations of 0Á25-1% (v/v), with a bactericidal activity of approx.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%
“…As a preservative agent, 1,2‐hexanediol must meet safety requirements (Johnson et al . ; Levy et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation